Antibodies to citrullinated α-enolase peptide 1 and clinical and radiological outcomes in rheumatoid arthritis. Issue 6 (1st March 2011) - Fisher, Benjamin A; Plant, Darren; Brode, Monica; van Vollenhoven, Ronald F; Mathsson, Linda; Symmons, Deborah; Lundberg, Karin; Rönnelid, Johan; Venables, Patrick J
Abstract : Introduction: The anticyclic citrullinated peptide 2 (anti-CCP2) assay is a generic test for antibodies to citrullinated proteins, among which there is a subset of about 50% with antibodies to citrullinated enolase peptide 1 (CEP-1). The anti-CEP-1 positive subset is strongly associated with the HLA-DRB1 shared epitope and its interaction with smoking. Objective: To investigate whether anti-CEP-1 antibodies may be helpful in predicting outcome. Methods: Anti-CEP-1 and anti-CCP2 antibodies were measured in two prospective cohorts of patients (Karolinska n=272, Norfolk Arthritis Register (NOAR) n=408) with early rheumatoid arthritis (RA). Outcomes measured were C-reactive protein, erythrocyte sedimentation rate, visual analogue scales for pain and global assessment of disease activity, Health Assessment Questionnaire, physician's assessment, swollen and tender joint counts and radiological progression. Results: Anti-CCP2 antibodies were present in 57% and 50%, and anti-CEP-1 in 27% and 24% of the Karolinska and NOAR cohorts, respectively. Importantly, no statistically significant differences in clinical outcomes were demonstrated between the anti-CEP-1−/CCP2+ and the anti-CEP-1+/CCP2+ subsets in either cohort, or in radiological outcomes in the Karolinska cohort. Conclusion: Although antibodies to specific citrullinated proteins may have distinct genetic and environmental risk factors, the similarity in clinical phenotype suggests that they share common pathways in the pathogenesis of joint disease in RA.